2017
DOI: 10.1055/s-0040-1708720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music Therapy on Pain and Quality of Life among Cancer Survivors

Abstract: Background: Cancer is one of the ten leading cause of death in India. Cancer patients usually present with moderate to severe pain which results usually from the cancer itself or from their treatment .To counteract pain complementary therapies are used along with the medical treatment. The most common used in the clinical setting is Music therapy; which is found to have a positive effect on the physical and psychological response of the patients. Objectives: To find the effectiveness of Music therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…Non comparable findings were observed in a pilot study by Bareh and D'Silva [22], where the results showed no significant difference (p>0.05) in quality of life of patients with breast cancer undergoing chemotherapy before and after music therapy.…”
Section: Discussionsupporting
confidence: 58%
“…Non comparable findings were observed in a pilot study by Bareh and D'Silva [22], where the results showed no significant difference (p>0.05) in quality of life of patients with breast cancer undergoing chemotherapy before and after music therapy.…”
Section: Discussionsupporting
confidence: 58%
“…The types of nursing support expected to promote comfort and relieve local tension included relaxation therapy using virtual reality (VR) in two studies [55,56] (one RCT), massage therapy in eight studies [57][58][59][60][61][62][63][64][65] (four RCTs), aromatherapy massage in one RCT [60], music therapy in six studies [44,[66][67][68][69][70] (five RCTs), reflexology in five RCTs [43,65,[71][72][73], poetry appreciation in one RCT [68], and foot bathing in one RCT [74].…”
Section: Resultsmentioning
confidence: 99%
“…Music consists of several genres and those that are often used in research are classical, popular, Chinese music, and instrumental (24,25). Music stimulates the body to release endorphins that can fight pain by affects the patients' feelings or mood so that the patients have their own way of dealing with illness (26).…”
Section: Discussionmentioning
confidence: 99%